Self-determined Motivation, Satisfaction with Life and Social integration of Adapted Sports Athletes in Athletics - Ferreira, Denise (2019)
The sport in your strand adapted contributes to significant improvements in functionality, social autonomy and the quality of life of individuals with disabilities. The objective of this study was to evaluate the Self- determined Motivation, Basic Psychological needs, satisfaction with life and Affections produced between sports athletes and regular sport in athletics, evaluating also the lack of Social integration of athletes with disabilities. 127 athletes attended, where 100 are practitioners of athletics at regular (air) between 15 and 48 years (M = 19.38 ± 6.70), and the remaining 27 of adapted athletics (AA) between 16 and 50 years (M = ± 10.25 34.48). As data collection instruments used questionnaires and semi-structured interview. The results obtained revealed that the AA athletes showed higher average values of autonomous motivation, satisfaction with life and positive effects, compared to athletes who presented air higher average values of motivation controlled, motivation and negative effects. Through the interviews we found that the integration in sport adapted by athletes with disabilities made had won greater autonomy and greater self-confidence, recognizing their potential, limitations and values, facilitating your integration in society.